2003
DOI: 10.1021/jf0345292
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and Formation Dynamic of Oak-Related Volatile Compounds from Different Volume Barrels to Wine and Their Behavior during Bottle Storage

Abstract: The extraction rate of furfuryl aldehydes, guaiacol, and 4-methylguaiacol, cis- and trans-oak lactone, and vanillin and the formation rate of furfuryl alcohol and the volatile phenols 4-ethylguaiacol and 4-ethylphenol have been studied in wines matured in different capacity oak barrels (220, 500, and 1000 L). Also, the behavior of these compounds during 1 year of wine bottle storage was followed. The lactones were extracted at a linear rate with large differences that depended on barrel volume. Those compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(46 citation statements)
references
References 21 publications
4
42
0
Order By: Relevance
“…Previous studies [33,34] showed that oak lactones are produced under strong acid hydrolysis and pyrolysis conditions. Pérez-Prieto et al [35] found that oak lactone concentrations increased during 270 days of barrel maturation and then continued to increase during the first 180 days of bottle storage, that is, after removal from oak contact. The generation of additional quantities of oak lactone during cooperage, bottle storage, led to the realization that oak lactone occurs in oak wood in both free and Among phenolic aldehydes, vanillin considered to have the most important influence on wine aroma.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies [33,34] showed that oak lactones are produced under strong acid hydrolysis and pyrolysis conditions. Pérez-Prieto et al [35] found that oak lactone concentrations increased during 270 days of barrel maturation and then continued to increase during the first 180 days of bottle storage, that is, after removal from oak contact. The generation of additional quantities of oak lactone during cooperage, bottle storage, led to the realization that oak lactone occurs in oak wood in both free and Among phenolic aldehydes, vanillin considered to have the most important influence on wine aroma.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, the content of furanic aldehyde compounds was lower than expected . 2-Furfuraldehyde tends to increase even during aging in bottles, and this was also observed in wine aged in oak barrels for nine months and then in bottles for one year (Pérez-Prieto, López-Roca, Martínez-Cutillas, Pardo-Mínguez, & Gómez-Plaza, 2003). 4-Ethylphenol is produced by non-Saccharomyces yeasts and it is undesirable for aroma because it introduces an organoleptic defect (Martorell, Martí, Mestres, Busto, & Guasch, 2002).…”
Section: Influence Of the Different Woods On The Aromatic Profile Of mentioning
confidence: 96%
“…5-Methylfurfural was only detected after 3 months of wood contact time. It has previously been demonstrated that furanic aldehydes may be reduced biologically during the ageing period to form their corresponding alcohols (Pérez-Prieto et al 2003a). Furfural may also be transformed into 2-furanmethanol through microbial or chemical mechanisms (GardeCerdan and Ancin-Azpilicueta 2006).…”
Section: Furfural and 5-methylfurfuralmentioning
confidence: 99%